Economic growth in oil-exporting countries: Do stock market and banking sector development matter? Evidence from Nigeria - Chinazaekpere Nwani; Jacob Bassey Orie (Cogent Economics & Finance, 2016)
This study empirically examines the independent effects of stock market and banking sector development on economic growth in Nigeria over the period 1981-2014 using the autoregressive distributed lag (ARDL) approach to co-integration analysis. Controlling for the possible effects of crude oil price and trade openness on economic activities in Nigeria, this study found both stock market and banking sector development insignificant in influencing economic growth in Nigeria. In general, the results highlight the weakness of the Nigerian financial sector in stimulating economic growth through resource mobilisation and allocation and the dominant role of the oil sector in economic activities in Nigeria.
Keywords: G20; G10; O11; Q32; 330; stock market; banks; economic growth; oil price; oil-exporting countries; Nigeria; ARDL